Identitet, konflikt og veien hjem. Stemmer i nyere samisk ungdomslitteratur - Kolberg, Asbjørn Rørslett (Nordlit, 2022)
The article explores how Sami identity and belonging is thematised in four novels for young people: Slepp meg (2018) and Det Sara skjuler (2019) by Kathrine Nedrejord, Hamburgerprinsessa ([2017] 2019) by Saia Stueng and Bara Dra (2018) by Ann-Helén Laestadius. The authors are Sami; Saia Stueng writes in the Sami language, Nedrejord and Laestadius in Norwegian and Swedish respectively. The novels are read with emphasis on voice, conceptualisation of body and place, and identity development in the light of traditional narrative patterns. Furthermore, the novels are discussed in educational, decolonizational and postcolonial perspectives suggesting that the texts represent what the literary scholar Homi K. Bhaba calls the third space, where cultural identities are dynamic and subject of negotiation.